OPTIMIZATION AND STUDY OF GRID IMPACT ON PHOTOVOLTAIC INSTALLATION â CONNECTED 785 MVA STEAM TURBINE POWER PLANT FOR INDUSTRY - Wijaya Nababan, Benny
The integration of solar power as a variable renewable energy (VRE) source has become increasingly popular in industrial grids. However, this also poses many challenges such as grid stability, intermittent energy supply, and meeting the demands of the industrial process. As a result, there is a need to find the optimum installation and operational points for PV systems by considering various constraints, such as generation limitations, spinning reserve, and steam demand. To address these challenges, this paper proposes a methodology for finding the optimal installation and operational points for PV systems in industrial grids. The methodology considers various constraints, such as generation limitations, spinning reserve, and steam demand, to ensure that the PV system can meet the plant process operating requirements. The paper also investigates the intermittent of renewable energy on the security and stability of the power system with several options for solar capacity. The study analyzes the modeling and simulation of 8 steam turbine generators and PV systems using PowerFactory Digsilent, a power system software that offers various solutions for power system analysis and simulation. Additionally, the study of unit commitment and economic dispatch is also carried out using solver to analyze actual power measurement data from power plants, based on the integration of variable renewables. The research findings indicate that the optimal installation of up to 50 MWp of solar panels can be achieved gradually while considering constraints such as spinning reserve equivalent to the largest generator and the system's ability to handle high-power equipment starting, if required. The results of this study provide valuable insights into the integration of renewable energy sources in industrial grids, which can help inform future energy policies and strategies.